2021
DOI: 10.1002/osp4.532
|View full text |Cite
|
Sign up to set email alerts
|

Differences in ​the proportion of children meeting behavior guidelines ​between summer ​and school by socioeconomic status and race

Abstract: Objective: Children who fail to meet activity, sleep, and screen-time guidelines are at increased risk for obesity. Further, children who are Black are more likely to have obesity when compared to children who are White, and children from low-income households are at increased risk for obesity when compared to children from higher-income households. The objective of this study was to evaluate the proportion of days meeting obesogenic behavior guidelines during the school year compared to summer vacation by rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 52 publications
3
8
5
Order By: Relevance
“…Specifically, we found that reductions in physical activity during the pandemic were larger for samples at higher latitudes, corresponding to regions of the globe where restrictions coincided with a seasonal transition into the summer months. This finding is consistent with prepandemic data showing that unstructured summer days during school holidays can have negative associations with both academic and physical health behaviors, often referred to as the “summer slide.” A recent estimate of such a summertime reduction of moderate-to-vigorous physical activity of 11.4 minutes is substantially lower (~ 50%) than the pooled estimate from our meta-analysis, however. This suggests a substantial intensification during the pandemic of the usual summer slide into physical inactivity, which warrants particular attention from policy makers seeking to help children “sit less and play more,” as targeted initiatives will be needed as children emerge into the summer months.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Specifically, we found that reductions in physical activity during the pandemic were larger for samples at higher latitudes, corresponding to regions of the globe where restrictions coincided with a seasonal transition into the summer months. This finding is consistent with prepandemic data showing that unstructured summer days during school holidays can have negative associations with both academic and physical health behaviors, often referred to as the “summer slide.” A recent estimate of such a summertime reduction of moderate-to-vigorous physical activity of 11.4 minutes is substantially lower (~ 50%) than the pooled estimate from our meta-analysis, however. This suggests a substantial intensification during the pandemic of the usual summer slide into physical inactivity, which warrants particular attention from policy makers seeking to help children “sit less and play more,” as targeted initiatives will be needed as children emerge into the summer months.…”
Section: Discussionsupporting
confidence: 89%
“…72 A recent estimate of such a summertime reduction of moderate-to-vigorous physical activity of 11.4 minutes 69 is substantially lower (~50%) than the pooled estimate from our meta-analysis, however. This suggests a substantial intensification during the pandemic of the usual summer slide into physical inactivity, 70 which warrants particular attention from policy makers seeking to help children "sit less and play more," 73 as targeted initiatives will be needed as children emerge into the summer months.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to previous studies reporting children sleep longer in the summer holidays, 16,17 Children had poorer diet quality in the summer holidays; however, there was no notable or significant change in energy intake. These findings are consistent with studies reporting children consumed less fruit and vegetables and more added sugars during the summer holidays versus school time, 14 but are in contrast with studies concluding no dietary differences 18,36 or that children consumed more fruit during the summer holidays.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings of the current study align with previous studies that have found children spent more time on screens during the summer holidays compared with the school year 14,16–18,36 . This finding is expected given the presence of the 6‐h school day, which limits recreational screen time opportunities to mainly before and after school and on weekends.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation